(untitled) (Dhaka University Journal of Science, 2021)
An attempt has been made to assess the capability of the Weather Research and Forecasting (WRF) model in simulating the track and landfall characteristics of Tropical Cyclone (TC) Fani (25th April – 05th May 2019) over the Bay of Bengal (BoB). WRF model has conducted on a single domain of 10 km horizontal resolution using Global Data Assimilation System (GDAS) data (0.250×0.250). The model predicted outcomes show auspicious agreement with the observed datasets of the Bangladesh Meteorological Department (BMD) and India Meteorological Department (IMD). It is found that the diminished lead time of the model run plays a crucial role in delivering good consistency with the minimum forecast uncertainty. A strong correlation between the track and intensity forecast deviations has also been determined. According to the results, the model simulation which captures the minimum deviation in the intensity forecast also ensures better track prediction of the system. The feasibility of the track and landfall forecast by the model even up to 27 hr advance is reasonably well. Finally, it can be decided that the model is capable to predict the cyclonic storm Fani precisely and it can be chosen confidently for future events over the BoB. Dhaka Univ. J. Sci. 69(2): 101-108, 2021 (July)